Characterization of immunosensor for early detection of cucumber mosaic virus (CMV) detection in chili - Shahrul Aizzam Ariffin author (School of Nano Electronic Engineering, Universiti Malaysia Perlis, 2017)
The specific objectives of this research are ; to study the effect of abinding process for sensitivity measurement of the reaction between screen-printed carbon electrode (SPCE) and biomolecule samples ; to assess the performance of surface modification of inorganic material (carbon) for better attachment of gold nanoparticles conjugate on the inorganic surface for immobilization and binding process ; to explore the performance and the proposed of screen printed carbon electrode sensor to function as biosensor for detection of biomolecule samples for sensitivity and selectivity detection using cyclic amperometric measurement ; to study gold nanoparticles performance and functionality in detection, reliability and efficiency toward biomolecule field samples for immobilization and binding process ; to study cross-reactivity at various biomolecule samples to verify the sensor does not react to other diseases using cyclic amperometric measurement.